Meta-analysis: The Impact of PjBL on Students' Creative Thinking Skills in Physics Education - Rohmatika, Ria; Yuliani, Hadma; Annovasho, Jhelang (Lensa: Jurnal Kependidikan Fisika, 2024)
Education needs to enhance creative thinking skills, which are crucial in the era of the Fourth Industrial Revolution. However, traditional teacher-centered learning strategies have proven ineffective in fostering these skills, especially in challenging subjects like physics. The use of Project-Based Learning (PjBL) has been shown to improve students' creative thinking skills in physics education. This study aims to explore the impact of PjBL on students' creative thinking skills across various indicators in physics education by synthesizing findings from related research. The study employs a meta-analysis method, collecting empirical data using Google Scholar through Harzing’s Publish or Perish 8 and Mendeley reference management software. The search yielded 28 articles from 2014-2024, with 13 articles meeting the inclusion criteria and providing sufficient data to calculate effect size. The results show an effect size of 1.03 (high). The effect size interpretation indicates that PjBL has an 84% impact on students' creative thinking skills. Additionally, 19 research articles observed creative thinking indicators influenced by PjBL, with elaboration being the highest and flexibility the lowest. It is concluded that the application of the PjBL model significantly affects students' creative thinking skills in physics education.